Eksplorasi Self-esteem Anggota Sanggar Tari Jitera Kreasi Indonesia: Peran Komunitas dalam Pembentukan Kepercayaan Diri - Sien Karsiya Sidik; Nadhira Rasendriya Pangestu; Asti Setyaningsih (Jurnal Konseling dan Psikologi Indonesia, 2026)
Self-esteem and self-confidence are important aspects of psychological development in adolescents, particularly during the process of identity formation. Artistic activities, such as dance, can serve as a medium for self-expression and for strengthening self-worth through training experiences, performance, and social interaction within artistic communities. This study aims to explore how active involvement of adolescents in the Sanggar Jitera Kreasi Indonesia dance community shapes self-esteem, particularly through the dimensions of self-competence and self-liking. This study employed a qualitative phenomenological approach involving four active dance studio members aged 15–18 years who had participated in the community for at least one year. Data were collected through online in-depth interviews and analyzed using thematic analysis, including transcription, repeated reading, coding, categorization, and theme development. The findings indicate that participation in the dance studio enhances self-competence through mastery of dance techniques and continuous practice. Self-liking also increased due to social support from instructors, peers, and family, which strengthened self-acceptance and pride in one’s identity as a dancer and fostered self-confidence. Adolescents were able to manage feelings of inferiority and social comparison within a supportive environment. These findings suggest that dance studio communities play a significant role not only in developing dance skills but also in enhancing adolescents’ self-esteem. Supportive social environments, experiences of achievement, and validation from artistic communities are important factors in identity formation and self-worth development. Future studies are recommended to involve larger samples, use mixed-method approaches, and explore the roles of instructors and group dynamics to deepen understanding of the contribution of artistic communities to adolescent psychological development.